Biochanin a modulates steroidogenesis and cellular metabolism in human granulosa cells through TAS2Rs activation: a spotlight on ovarian function - Francesca Paola Luongo; Sofia Passaponti; Alesandro Haxhiu; Irene Ortega Baño; Rosetta Ponchia; Giuseppe Morgante; Paola Piomboni; Alice Luddi (Reproductive Biology and Endocrinology)
Abstract Background Endocrine-disrupting chemicals (EDCs) interfere with the endocrine system and negatively impact reproductive health. Biochanin A (BCA), an isoflavone with anti-inflammatory and estrogen-like properties, has been identified as one such EDC. This study investigates the effects of BCA on transcription, metabolism, and hormone regulation in primary human granulosa cells (GCs), with a specific focus on the activation of bitter taste receptors (TAS2Rs). Methods Primary human GCs from 60 participants were treated with 10 µM BCA, and selective antagonists were used to block TAS2R activation. The study assessed the expression of TAS2R14 and TAS2R43, and analyzed the impact on StAR and CYP17A1 gene expression. Intracellular calcium levels, lipid droplet size, and mitochondrial network complexity were measured to evaluate cellular metabolism and energy dynamics. Results BCA treatment significantly upregulated TAS2R14 and TAS2R43 expression, leading to a 70% increase in StAR mRNA levels and a twofold increase in CYP17A1 expression (p < 0.05). These effects were reversed by TAS2R antagonists. Additionally, BCA treatment decreased intracellular Ca2+ levels (p < 0.01) and reduced lipid droplet size (p < 0.001), both of which were counteracted by antagonists. Enhanced mitochondrial network complexity (p < 0.001) was also observed, suggesting increased mitochondrial fusion and improved cellular energy dynamics. Conclusion The findings indicate that BCA modulates transcriptional and metabolic processes in GCs through the activation of TAS2Rs, highlighting their role in endocrine regulation. The statistically significant results emphasize the relevance of further exploring the effects of EDCs like BCA on reproductive health. Collaborative research efforts are essential to address and mitigate the adverse impacts of EDCs on fertility.